Assessment of the Stability of Bev Lhd Loader - Bołoz Łukasz; Kozłowski Artur; Horak Wojciech (Management Systems in Production Engineering, 2022)
The article concerns the computational model for analysing the stability of the BEV LHD loader. Works were carried out to develop an innovative, light battery-powered loader, which was the subject of an R&D project implemented in cooperation with Bumech S. A. Compared to the existing solutions of loaders with similar load capacity, this one is distinguished by the use of an individual electric drive in each wheel and a replaceable battery. A physical and mathematical model was developed taking into account the specificity of the BEV LHD loader. In the model, the masses of the battery, individual drives, the platform and excavated material are taken into account separately. The developed model allows determining the loader wheel pressure on the floor, depending on the location of its components’ centres of gravity, the turning angle of the machine, the amount of excavated material in the bucket and the position of the bucket. The input parameters also include the longitudinal and transverse excavation slope angles. In addition, the model enables determining the inner and outer turning radius of the loader. To verify the theoretical model, dynamic simulation tests were carried out. The results of simulation analyses confirmed the correctness of the developed theoretical model. The model was used to prepare a calculation sheet for analysing the stability on the basis of the adopted parameters. In the article, selected results of the conducted stability analyses have been presented, along with the proposed parameters ensuring the loader’s stability. The developed theoretical model enables a quick assessment of the loader’s stability, which, due to a number of innovative solutions, differs from existing designs. The structure of the loader at the design stage is subject to numerous modifications, which affect the distribution of the centres of gravity of individual components. The developed model of the loader is a useful, parameterized tool that allows assessing the stability and the values of the turning radii of the machine.